A New Finite Interval Lifetime Distribution Model for Fitting Bathtub-Shaped Failure Rate Curve. (26th March 2015) - Wang, Xiaohong; Yu, Chuang; Li, Yuxiang
Abstract : This paper raised a new four-parameter fitting model to describe bathtub curve, which is widely used in research on components' life analysis, then gave explanation of model parameters, and provided parameter estimation method as well as application examples utilizing some well-known lifetime data. By comparative analysis between the new model and some existing bathtub curve fitting model, we can find that the new fitting model is very convenient and its parameters are clear; moreover, this model is of universal applicability which is not only suitable for bathtub-shaped failure rate curves but also applicable for the constant, increasing, and decreasing failure rate curves.